Design and development of critical thinking learning strategy in integral calculus - Nurul Shida; Abdul Halim Abdullah; Sharifah Osman; Norulhuda Ismail (Institute of Advanced Engineering and Science, 2023)
Difficulty in understanding problem solving is due to the absence of critical thinking. Students lack knowledge in assessing critical thinking during problem solving. Hence, there is a need to study critical thinking infused through a learning strategy to enhance problem solving. Critical thinking (CThink) is a learning strategy designed which combines critical thinking and Integral Calculus. The development process of CThink combines the critical thinking process and questioning for critical thinking using the analysis, design, development, implementation, and evaluation (ADDIE) model. In the learning strategy, questions were applied based on CThink processes which consist of interpretation, analysis, inference, evaluation, explanation, and self-regulation. Besides, different questioning for CThink is presented based on the critical thinking process. CThink has achieved a content validity of 94.12% with a coefficient value of 0.94, and the value is above 70% or 0.70. Based on the result, the contents in the CThink are considered of good validity. From the calculation of the percentage from the expert given score, CThink has achieved the validity measurement for the language of 97.50% with a coefficient value of validity is 0.975, which is above 70 or 0.70. Based on the result, the activities and syllabus used in CThink achieved good validity measurements. The experts concluded that this CThink meets the content of Integral Calculus, in line with the level of polytechnic students, allowing students to think critically to solve problems as well as activities in CThink help to enhance student problem solving.